Emergence of Uncertainty: A Microgenetic Study of the Preschool Period, Sabbatical Leave Report - Kahlbaugh, Patricia (2003)
Keywords: dept.psy; faculty_collection; sabbatical_report

Visual influences on the internal structure of phonetic categories - Brancazio, L; Miller, JL; Pare, MA (Perception & Psychophysics, 2003)
Previous work has demonstrated that the graded internal structure of phonetic categories is sensitive to a variety of contextual factors. One such factor is place of articulation: The best exemplars of voiceless stop consonants along auditory bilabial and velar voice onset time (VOT) continua occur over different ranges of VOT! (Volaitis & Miller, 1992). In the present study, we exploited the McGurk effect to examine whether-visual information for place of articulation also shifts the best-exemplar range for voiceless consonants, following Green and Kuhl's (1989) demonstration of effects of visual place of articulation on the location of voicing boundaries. In Experiment 1, we established that /p/ and /t/ have different best-exemplar ranges along auditory bilabial and alveolar VOT continua. We then found, in Experiment 2, a-similar shift in the best-exemplar range for /t/ relative to that for /p/ when there was a change in visual place of articulation, with auditory place of articulation held constant. These findings indicate-that the perceptual mechanisms that determine internal phonetic category structure-are sensitive to visual, as well as to Auditory, information.
12 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000183134600008
Keywords: Adolescent; Adult; Female; Humans; Male; Middle Aged; Phonetics; Random Allocation; Speech Perception; Time Factors; Visual Perception; Voice; adolescent; adult; article; dept.psy; female; human; male; middle aged; phonetics; randomization; speech perception; time; vision; voice

Effects of free-food deliveries and delays on choice under concurrent-chains schedules. - Mazur, James E (Behavioural Processes, 2003)
Pigeons responded on a concurrent-chains schedule with two equal variable-interval (VI) schedules as initial links and delays to food of 3 and 12 s as the two terminal links. In even-numbered sessions, no other reinforcement schedule was present, and all pigeons showed a strong preference for the response key that had the shorter, 3-s terminal-link delay. In odd-numbered sessions, the initial links were interrupted at random times by one of three different types of events. When the interruptions were immediate food deliveries, the response percentages increased on the key that had the 3-s delay. When the interruptions were 30-s delays followed by food, the response percentages remained approximately unchanged. When the interruptions were 30-s delays with no food, the response percentages decreased. The results were used to compare the predictions of different mathematical models of concurrent-chains performance. The results favored models that assume that preference is determined by the relative amount of advantage that is gained when a terminal link is entered. (C) 2003 Elsevier B.V. All rights reserved.
3 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E.. Psychology Department, Southern Connecticut State University, 06515, New Haven, CT, USA
Keywords: Choice; Columba; Concurrent chains; Free food; Key peck; Pigeons; Reinforcer delay; animal behavior; animal experiment; article; controlled study; decision making; dept.psy; food; food deprivation; mathematical model; nonhuman; pigeon; prediction; preference behavior; reinforcement; stimulus response